Pit and Fissure Sealants as a Viable Preventive Tool for Dental Caries - Priyanka. L. Kalimireddy; Susant Mohanty (Indian Journal of Forensic Medicine & Toxicology, 2021)
Dental caries remains to be a global disease burden and the current ways of preventing it are throughmaintenance of good oral hygiene, watching over the diet intake and pit and fissure sealant application. Pitand fissure sealants are still underused in dental practice. With the availability of the various type of sealantsranging from glass ionomer sealants to resin sealants, we need to improvise our preventive protocols fordental caries. This article provides crisp and compact information on the current status and usage of dentalsealants to encourage the fraternity to use it more often.